Design and Build of a Temperature Monitoring System for Charcoal Burning Pipes Using Arduino Uno - Setyawan, Reynaldi Teguh; Bambang, Bambang; Rahma, Yosie (ABEC Indonesia, 2024)
Charcoal burning is a traditional method widely used in industries such as power generation, steel production,and manufacturing. This process involves high-risk equipment components, such as pipes that have a certain meltingpoint limit, so continuous temperature monitoring is very important to maintain operational efficiency and safety.Anjangg village, as a producer of charcoal from mangrove tree trunks, faces air pollution problems due to the smokeproduced during the burning process. As a solution, a tool has been developed that can convert smoke into liquid (liquidsmoke). However, the high temperature of the smoke poses a risk to the PVC pipe material used in liquid smokecondensers which can melt at a temperature of 85℃. The tool that will be made in this research is a tool that can monitorthe temperature of the pipe to help maintain the durability of the condenser pipe material. This monitoring system tool isrun using an automatic Arduino Uno microcontroller system and uses a type K thermocouple temperature sensor as atemperature detection tool in the pipe. The test results show that the system is successful in detecting temperatures up to83.75℃ well, with consistent voltage when detecting smoke or not.